The Effects of Constant Illuminance at Multiple Temperatures Towards Muscle Activities for Rubber Scrap Industries - Che Mohammad Nizam, Che Mohammad Nizam; Ahmad Rasdan Ismail, Ahmad Rasdan Ismail; Ezrin Hani Sukadarin, Ezrin Hani Sukadarin; Norlini Husshin, Norlini Husshin (semarak ilmu, 2023)
The objective of this study is to determine the effect of ergonomic factors, such as temperature and illuminance level towards muscle activities through repetitive loading and unloading tasks. The study settings are in Ergonomic Laboratory Chamber and a rubber factory. Six male respondents that participated in this study wear Electromyography (EMG) device on both sides of their bodies to measure muscle fatigue. EMG output signal data were analysed to determine the correlation between muscle activities with illuminance level and temperature. At constant 500 lux illuminance level and 24˚C temperature, respondent’s body shows optimum correlation between left sides and right sides. On the contrary, findings show unbalanced correlation at 19˚C and 32˚C which indicate one side of the body is using too much energy for the task.